Hydrography of the inner shelf offshore Bahía Blanca estuary - Cuadrado, Diana Graciela (2002)
In this paper a quantitative description of the hydrographic regime in the inner shelf offshore Bahia Blanca and Colorado River estuaries based on temperature, salinity, suspended matter and currentvelocity data is described. Both estuaries contribute in different ways to the physical characteristics of the environment. The Colorado River estuary is the major source of freshwater into the EI Rincon area, whereas the Bahia Blanca estuary is a source ofrelatively warm and salty water. Accordingly, the influence of both estuaries in the distribution of the water properties is observed. It the Colorado River into the inner shelf was quantified.The processes involved at the Bahia Blanca Estuary is the first time the influence of the discharges the first time the influence of the discharge of the Colorado River into the inner shelf was quantified. The processes involved at the Bahia Blanca Estuary are different from the typical estuary pattern. Exchange processes between estuaries andembayments with offshore waters are seldom analyzed in detail, especially in relation to the circulation of the inner shelves. With the information obtained by two currentmeters two regimes are identified, one associated with the estuarine waters and one with the coastal waters. By means of statistical analysis (PCA), the importance of two measured parameters (salinity and suspended matter) has been determined in the study zone: a nearshore zone affected by estuarine dsicharge, and an offshore zone mixed by strong winds. A comparison on the wind power needed to destroy stratification in the water measured in South Atlantic Bight with the results here obtained, demostrate that in El Rincón area the wind power is much higher during "sudestadas", typical storm events in the region.